The pragmatics of education journals: the case of the International Journal of Educational Development - McGrath, Simon; Mason, Mark (2010)
This article discusses some of the pragmatics and politics of academic journal publishing within the context of the contemporary higher education and publishing political economy. The case of the International Journal of Educational Development(IJED) is considered, and some implications drawn for the Southern African Review of Education (SARE), given that the latter shares a focus on educational development with the former. The authors, who are editors and board members of both journals, conclude that SARE would probably benefit in many ways by seeking a partnership, such as IJED has, with an established and highly regarded international academic publishing house.